Development of Bio Batteries Utilizing Coconut Dregs and Pineapple Extract as Alternative Energy Sources - Toruan, Parmin Lumban; Wahyuni, Dita Putri; Rahmawati, Rahmawati; Atina, Atina (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Coconut and pineapple dregs contain ions that can be effectively used as energy sources. This study aims to evaluate the electricity generated from varying compositions of coconut dregs and pineapple juice in bio-batteries. The bio-battery paste is created using different ratios of coconut dregs and pineapple juice, along with electrodes (aluminum and graphite). An experimental method was employed. The results indicated that the highest voltage of 0.54 V and a current of 0.71 mA were achieved with 40 ml of pineapple juice added to the coconut dregs, whereas the lowest voltage of 0.40 V and a current of 0.01 mA were observed without adding pineapple juice. For the pineapple juice concentration, the highest voltage of 0.51 V and a current of 0.91 mA were obtained with 10 grams of coconut dregs, while the lowest voltage of 0.44 V and a current of 0.31 mA occurred with 40 grams of coconut dregs. The concentration of coconut dregs and pineapple juice significantly affects the voltage produced, while the current is significantly influenced by the concentration of coconut dregs but not by the concentration of pineapple juice.